Perbedaan Tingkat Kecemasan Caregiver Pasien Skizofrenia Tipe Disorganized Dengan Tipe Katatonik Di RS Jiwa Daerah Surakarta - Wibowo, Antonius Setyo; Syamsulhadi, Muchammad; Probandari, Ari Natalia (Nexus Kedokteran Klinik, 2014)
Background : Schizophrenia is a clinical syndrome of severe mental disorders characterized by abnormal perception in the form of hallucinations, delusions, psychiatric behavior deviations, unusual beliefs, and mind distortions. Caregiver, someone who responsible to treat the patient will feel burden, include anxiety. This research aims to know the anxiety level difference between disorganized type and catatonic type of schizophrenia caregiver in RS Jiwa Daerah Surakarta. Methods : This study was a descriptive analytic study with a cross sectional approach, conducted in the RS Jiwa Daerah Surakarta. The subjects Â were taken using consecutive sampling method. The subjects were divided into two groups, disorganized type and catatonic type of schizophrenia caregiver. The subjects filled out the (1)Informed Consent, (2)Study Questionnaire, (3)L-MMPI Questionnaire, (4)T-MAS Questionnaire. If the subject did not meet the criteria of inclusion and exclusion, and the result of the L-MMPI questionnaire â¥ 10, the subject could not be selected. The 35 data consisted of 25 disorganized type and 10 catatonic type of schizophrenia caregivers were analyzed using Fisherâs Exact Test. Results : This study demonstrated there is no difference of anxiety level between disorganized type and catatonic type of schizophrenia caregiver in RS Jiwa Daerah Surakarta which was shown by p = 0.264 (p > 0.05). Conclusions : There was no difference anxiety level between disorganized type and catatonic type of schizophrenia caregiver in RS Jiwa Daerah Surakarta. Keywords: caregiver, schizophrenia, disorganized type, catatonic type, anxiety levelÂ